(untitled) (International Journal of Nursing Education, 2025)
Objective To explore the current situation and factors influencing the career adaptability of nursing students in practice, and to provide a theoretical basis for career education of clinical nursing students. Methods: From October to December 2023, 189 nursing students from colleges and universities who were interning at a Class III, Grade A general hospital in Henan Province were selected as survey participants. The General Information Questionnaire and the Career Adaptability Questionnaire for College Students were used to investigate these nursing interns. Factors affecting the career adaptability of nursing interns were analyzed using single-factor and multiple linear regression analyses. Results: The career adaptability score of nursing interns was 132.77 ± 22.49. Single-factor analysis showed that whether parents were engaged in medical or nursing-related occupations and the reasons for choosing nursing had statistically significant effects on the career adaptability scores of nursing interns in future planning (p < 0.05). Multiple linear regression analysis revealed that whether parents were engaged in medical or nursing-related occupations and the reasons for choosing a nursing major were influencing factors of career adaptability among nursing interns. Conclusions: The career adaptability of nursing students is at a medium level. Specifically, whether their parents are engaged in medical or nursing-related occupations and the reasons for choosing a nursing major are influencing factors of career adaptability among nursing interns. It is recommended that nursing educators and clinical supervisors consider various factors to improve career resilience.